The Influence of Scientific Approach, Learning Motivation, and Student Responses on Statistical Learning Outcomes of STIE Muhammadiyah Mamuju Students - Rezky Novianti; Abdul Rajab (Universitas Negeri Makassar, 2020)
Education plays an important role in improving the quality of human resources in an effort to create general welfare and the intellectual life of the nation. Because of its very strategic role, issues related to the quality of education have always been the main discussion in government, for example related to the education system and the quality of educators. The cause of this stems from learning, where the learning approach has been centered on lecturers so that students tend to be passive. The purpose of this study was to determine how much influence the motivation to learn, student responses by using a scientific approach to statistical learning outcomes for STIE Muhammadiyah Mamuju students, which in the end is expected to have a quality learning process and an increase in learning outcomes. This type of research is ex post facto in the form of multiple linear regression analysis, combined with experimental research, namely statistical learning through a scientific approach involving the experimental class and the control class. Data collection techniques in this study were tests, questionnaires or questionnaires, observation and documentation. Initially, the sampling was carried out by purposive random sampling, the number of samples used in this study was 35% of the total population of 427 so that the sample was 114 (4 classes). However, because the Covid19 pandemic was increasing and it did not allow researchers to carry out optimally, a sample of 35 students was selected in the experimental class (1 class) and 34 students in the control class (1 class). Purposive said, because the selection according to the researcher had met the requirements, namely on the campus, the statistics subject lecturer had used a scientific approach in the learning process. And it is called Random Sampling, because in determining the sample is done randomly without any strata in the population. Then the data analysis method used is the validity and reliability test of the instrument, descriptive analysis, classical assumption test, and multiple linear regression analysis and hypothesis testing using the F test (simultaneous) and t test (partial) with the help of the SPSS for Windows program software (Statistical Package for Social Science) version 23.0 in processing research data. The results showed a significant effect both partially and simultaneously between learning motivation and student responses to statistical learning outcomes with a scientific approach to STIE Muhammadiyah Mamuju students, where learning outcomes for the experimental class (using a scientific approach) were better than control class with a conventional approach.